2010
DOI: 10.1021/jf1011775
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activities of Russula griseocarnosa sp. nov.

Abstract: Pileus and stipe of mushroom Russula griseocarnosa from South China were analyzed separately for chemical composition and antioxidant activities. The wild mushroom species proved to have antioxidant potential, using assays of reducing power, chelating effect on ferrous ions, scavenging effect on hydroxyl free radicals, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. The mushroom contained very useful phytochemicals such as phenolics, flavonoids, ergosterol, and beta-carotene. The phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 31 publications
(38 reference statements)
2
45
1
Order By: Relevance
“…Though other antioxidants were probably present in the mushroom extract, the amounts of ascorbic acid, b-carotene and lycopene found in the mushroom extract were very low (Chen et al, 2010). Therefore, phenolic compounds and flavonoids are considered to make a significant contribution to the mushrooms' antioxidant activity (Chen et al, 2010). Our results showed that essential oil fumigation treatments significantly delayed losses in phenolic compounds, and increased flavonoid contents in the mushrooms.…”
Section: Effect Of Essential Oil Fumigation On H 2 O 2 Content Omentioning
confidence: 66%
See 2 more Smart Citations
“…Though other antioxidants were probably present in the mushroom extract, the amounts of ascorbic acid, b-carotene and lycopene found in the mushroom extract were very low (Chen et al, 2010). Therefore, phenolic compounds and flavonoids are considered to make a significant contribution to the mushrooms' antioxidant activity (Chen et al, 2010). Our results showed that essential oil fumigation treatments significantly delayed losses in phenolic compounds, and increased flavonoid contents in the mushrooms.…”
Section: Effect Of Essential Oil Fumigation On H 2 O 2 Content Omentioning
confidence: 66%
“…Mushrooms are well known to possess antioxidant activity. This is mainly correlated with their phenolic and flavonoid compounds (Chen, Xia, Zhou, & Qiu, 2010). The mechanisms of action of flavonoids and phenolics are through scavenging and chelating processes or as free radical terminators (Cook & Samman, 1996).…”
Section: Effect Of Essential Oil Fumigation On H 2 O 2 Content Omentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been carried out into the biological activities of mushrooms and truffles (Breene 1990;Sagakami et al 1991;Chang and Buswell 1996;Hussain and Al-Ruqaie 1999;Murcia et al 2002;Janakat et al 2004Janakat et al , 2005Saleh 2006;Stanikunaite et al 2007;Fratianni et al 2007a;Al-Laith 2010;Chen et al 2010;Heleno et al 2010;Isabelle et al 2010;Janakat and Nassar 2010;Wang and Marcone 2011), which have been seen to possess medicinal properties, including the ability to inhibit platelet aggregation (Hokama and Hokama 1981) and blood cholesterol (Aletor 1995). Moreover, other research has suggested that mushrooms could form part of an antihypertensive diet (Manzi et al 1999); contribute to a reduction in blood glucose levels (Manzi and Pizzoferrato 2000); help in the prevention of infections caused by bacterial, viral, fungal and parasitic diseases (Breene 1990;Manzi and Pizzoferrato 2000); and have immunomodulation and anticancer effects (Ooi and Liu 2000) (see also Chap.…”
Section: Nutritional Compositionmentioning
confidence: 99%
“…More recently food scientists have focused special attention on the bioactivities of truffles, including their antioxidant, anticancer, antimicrobial, hepatoprotective, anti-mutagenic and anti-inflammatory activities (Breene 1990;Sagakami et al 1991;Chang and Buswell 1996;Hussain and Al-Ruqaie 1999;Isabelle et al 2010;Murcia et al 2002;Janakat et al 2004;Janakat et al 2005;Saleh 2006;Fratianni et al 2007;Stanikunaite et al 2007;Heleno et al 2010;Al-Laith 2010;Chen et al 2010;Janakat & Nassar 2010;Wang and Marcone 2011. The current paper provides an overview of Terfezia and Picoa investigations on their chemical and biological qualities, including antioxidant properties, during recent decades.…”
mentioning
confidence: 99%